Trunk hair removal treatment with diode laser 810nm in men population - Giovanni Cannarozzo; Beatrice Marina Pennati; Tiziano Zingoni (PAGEPress Publications, 2023)
In the last years, hair removal has been one of the most common treatments performed for aesthetic purposes, especially in women. Nevertheless, even if it is less popular, the demand within men population has raised. The study aimed to assess the acceptability of the diode 810 nm treatment for hair removal on the back and chest area in men thanks to the speed of treatment and the absence of undesirable effects. For this study, 20 patients were treated for hair removal. They were men with a mean age of 30.5 (±7.3). They underwent 4 treatment sessions at 40-day intervals on the trunk (chest and back area). Patients ranged between a Fitzpatrick phototype I (20%, 4/20) to IV (15%, 3/20) (40% were type II and 25% type III). Moreover, patients were asked to report pain intensity sensation with a Visual Analogue Scale (VAS). Overall, in the study population, a hair reduction of 80.6% (±2.8) was registered in the treated areas. The device described in this study was demonstrated to be highly efficient in extended body areas and on difficult-to-treat hair follicles like on the back and chest in the men population.